Understanding How Inequality in the Distribution of Income Affects Health - John W. Lynch and George A. Kaplan (J Health Psychol 1997; 2; 297, 1997)
Research on the determinants of health has almost exclusively focused on the individual but it seems clear we cannot understand or improve patterns of population health without engaging structural determinants at the societal level. This article traces the development of research on income distribution and health to the most recent epidemiologic studies from the USA that show how income inequality is related to age adjusted mortality within the 50 States. (r = -0.62, p =0.0001) even after accounting for absolute levels of income. We discuss potential material, psychological, social and behavioral pathways through which income distribution might be linked to health status. Distributional aspects of the economy are important determinants of health and may well provide one of the most pertinent indicators of overall social well-being.